Expanding Single Brackets 2

Easy

Medium

Difficult

Q1) 6(7x + 9) -5x + 3 =
Q1) 6(2x + 6) + 5(9x + 4 ) =
Q1) 10(10x + 7) - 2(5x -7 ) =
Q2) 8(10z + 2) +4z + 7 =
Q2) 7(5x + 4) + 8(8x -8 ) =
Q2) 9(4y -3) - 7(4y + 8 ) =
Q3) 3(8w + 5) -4w + 5 =
Q3) 3(10z -9) + 2(9z + 5 ) =
Q3) 6(7y + 5) - 4(8y + 2 ) =
Q4) 7(8w -5) +3w + 8 =
Q4) 3(10x + 7) + 8(4x -10 ) =
Q4) 5(5x + 8) - 3(8x -4 ) =
Q5) 7(8z -9) +10z + 9 =
Q5) 10(2z + 4) + 5(9z -2 ) =
Q5) 6(4w + 5) - 9(2w + 8 ) =
Q6) 4(7z -7) -6z -6 =
Q6) 3(7z -5) + 10(8z -5 ) =
Q6) 2(6w -4) - 2(3w + 6 ) =
Q7) 10(7w -3) +7w + 6 =
Q7) 7(9x + 10) + 5(4x -6 ) =
Q7) 4(4w + 7) - 2(6w -9 ) =
Q8) 7(8y -7) -3y + 9 =
Q8) 2(3x + 6) + 10(2x -2 ) =
Q8) 7(6z -3) - 2(6z + 5 ) =
Q9) 9(9z + 9) -9z + 3 =
Q9) 2(8z + 2) + 4(7z -8 ) =
Q9) 3(7y + 6) - 4(5y + 6 ) =
Q10) 10(7x + 6) +4x + 2 =
Q10) 3(9y + 8) + 10(6y + 7 ) =
Q10) 6(9z -4) - 2(10z -7 ) =